PENGEMBANGAN KEPEMIMPINAN KEPALA SEKOLAH MENGGUNAKAN COACHING GROW BERBASIS SMART UNTUK MENINGKATKAN PROFESIONAL GURU MELALUI KELOMPOK KERJA GURU (KKG) GUGUS DEWI SARTIKA - Urip Rahayu Slamet; Sitti Hartinah; Dewi Apriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a principal leadership model based on GROW coaching assisted by SMART principles to improve teacher professionalism through the Teacher Working Group (KKG) in the Dewi Sartika Cluster, Pemalang Regency. Many teachers still face difficulties in innovative learning, technology adaptation, and implementation of the latest curriculum. In addition, principals also face challenges in developing transformative leadership and coaching skills. This study uses a Research and Development (R&D) approach with a 4-D model: Define, Design, Develop, and Disseminate. The results of the study indicate that the application of SMART-based GROW coaching can improve teacher professionalism, both in terms of competence, work motivation, and collaboration in KKG. This article provides theoretical and practical contributions in developing coaching-based educational leadership in the era of digital transformation.